2019
DOI: 10.1002/ptr.6588
|View full text |Cite
|
Sign up to set email alerts
|

Berberine combined with stachyose induces better glycometabolism than berberine alone through modulating gut microbiota and fecal metabolomics in diabetic mice

Abstract: Berberine (BBR), a small alkaloid, is used as a hypoglycemic agent in China. Stachyose (Sta), a Rehmannia glutinosa oligosaccharide, acts as a prebiotic. This study aimed to evaluate whether BBR combined with Sta produced better glycometabolism than BBR alone, and explored the effects on gut microbiota and metabolomics. Type-2 diabetic db/db mice were administered BBR (100 mg/kg), Sta (200 mg/kg), or both by gavage once daily. Glucose metabolism, the balance of αand β-cells, and mucin-2 expression were amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Plovier et al [28] found that pasteurized Akkermansia muciniphila versus the live bacteria has an enhanced capacity to reduce fat mass development, insulin resistance and dyslipidemia in mice. Our previous study also manifested that BBR with Sta increased the abundances of phylum Verrucomicrobia and species Akkermansia muciniphila in the feces of db/db mice [4]. In addition, Verrucomicrobia is highly abundant in healthy subjects [29].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Plovier et al [28] found that pasteurized Akkermansia muciniphila versus the live bacteria has an enhanced capacity to reduce fat mass development, insulin resistance and dyslipidemia in mice. Our previous study also manifested that BBR with Sta increased the abundances of phylum Verrucomicrobia and species Akkermansia muciniphila in the feces of db/db mice [4]. In addition, Verrucomicrobia is highly abundant in healthy subjects [29].…”
Section: Discussionmentioning
confidence: 75%
“…Berberine (BBR), one of the main components of R. coptidis, is an isoquinoline alkaloid originally isolated from C. chinensis [2]. Several studies have shown that BBR has many advantageous biological roles in preclinical and clinical research, such as anti-in ammation, anti-insulin resistance, anti-hyperglycemia, anti-hyperlipidemia, anti-bacteria, and anti-diabetes [3,4]. BBR also ameliorates liver, cardiovascular, and renal disease that are associated with diabetes [3].…”
Section: Introductionmentioning
confidence: 99%
“…All of the 24 mice were sacrificed and the luminal contents were collected from the ileum (as the fecal samples) and snapfrozen in liquid nitrogen after 40 days at the end of treatment, followed by storage at −80°C. The gut microbiome in feces was assayed and the abundance and diversity of gut microbiota were analyzed using Illumina MiSeq sequencing (Major Bio-Pharm Technology, Shanghai, China) according to the standard protocol as previously described (Li et al, 2020). The sequence data were processed and analyzed on the free online Majorbio I-Sanger Cloud Platform (www.i-sanger.…”
Section: Gut Microbiota Profiling and Fecal Short-chain Fatty Acids Analysismentioning
confidence: 99%
“…In the experiment of atherosclerosis induced by HF diet in mice, Zhu et al [ 96 ] reported that BBR treatment increased the relate abundance of Akkermansia and Bacteroides in the gut, improved the number of goblet cells, restores the thickness of the colonic mucus layer, reduced metabolic endotoxemia and systemic inflammation, and then significantly ameliorated atherosclerosis. BBR can induce better glycometabolism through regulating the gut microbiota and fecal metabolomics in type-2 diabetic db/db mice, which is specifically manifested by decreased abundance of Saccharibacteria , Deferribacteraceae , Actinobacteria , and Firmicutes and increased abundance of Verrucomicrobia [ 97 ]. At present, only a limited number of studies examining the role of BBR through gut microbiota in HTN have been performed.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%